Nursing Quality: Exploring Completeness and Accuracy of Nursing Care Documentation at Hospital - Ni Putu Emy Darma Yanti; Ni Putu Leni Puswita Sari; I Ketut Dian Lanang Triana (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nursing Documentation has significant roles in order to enhancing patient safety. Thus, its accuracy and completeness should perfectly perform based on the standards. This study aims to evaluate the implementation of nursing care documentation among nurses in hospitals. This study employed non-experimental descriptive quantitative research with a retrospective approach and the samples chosen was 114 medical records that met the inclusion criteria using proportional stratified random sampling technique. The research instruments used is an observation sheet for a study documenting the nursing care standards implementation by The Ministry of Health of Republic Indonesia 2005, which has been modified by adding true and false points for each indicator assessed. The data analysis employed univariate analysis which is presented in the form of a frequency’s distribution. The study results found that most of the nurses were not able to complete the records correctly by 72,8% as well as grouping the data by 55,3% in the assessment aspects. In the diagnosis and the intervention aspects, most of the nurses are able to completing the documentation perfectly. On the other aspects, the study found that nurses are not able to complete the implementation that refers to the treatment plan by 67 or 58,8%. However, it is also found that the nurses are not able to documented the evaluation refers to objective by 58 or 50,9%. On the general documentation, most of the nurses still are not able to compete the records by standardized format (95;83,3%) as well as put the initials or name clearly and date in the documentation (58;50,9%).